Antimicrobial terpenoids from Lansium domesticum - Ragasa, Consolacion Y.; Labrador, Pamela; Rideout, John A (2006)
The air-dried fruit peel of Lansium domesticum Correa afforded five onoceroid triterpenes: 3ß- hydroxyonocera-8(26),14-dien-21-one (1), α,γ -onoceradienedione (2), lansiolic acid (3), lansionic acid (4) and lansioside C (5), while the air-dried seeds afforded 3 and germacrene D (6). Antimicrobial tests on 1-6 gave the following results. 2 has high activity against P. aeruginosa, while 1, 3, 4 and 5 have moderate activities against this microorganism. 5 and 4 have moderate and low activities against B. subtilis respectively, while 3 and 5 have low activities against S. aureus. All the compounds tested have moderate activities against C. albicans and A. niger, and low activities against T. mentagrophytes.
Keywords: Medicinal plants; Antifungal Agents